MILLENNIAL ENGLISH TEACHER IDENTITY: EMOTIONS AND RESILIENCE IN TEACHING - Imelda Woa Wene; Ouda Teda Ena (PROJECT (Professional Journal of English Education), 2023)
This study investigates the aspects of emotions and how those emotions affect the resilience of millennial English teachers in teaching. Millennial teachers face severe challenges in teaching. They meet different demands every day in school. This situation forces them to make challenging decisions every day. Therefore, it is crucial for them to have the ability to control emotions and resilience in teaching. In this study, the sampling strategy used to select participants was purposeful sampling. The participants were millennial English teachers who were teaching in a private elementary school. In gathering the data, the researchers applied a semi-structured interview with open-ended questions. The participants were asked about how they experienced their professional teaching careers, the struggles they encountered, especially in terms of emotions and how they overcome the problems they faced in the workplace. A narrative analysis was used in this study to analyze the interview data. The researchers analyzed the participants’ answers to find important points to answer the research questions. The results showed that the millennial teachers experienced complex emotions such as disappointment, and resentment when dealing with students, colleagues and students’ parents. However, those complex emotions did not make them leave their profession as teachers. Keywords:  Emotions; Resilience; Teacher Identity; Millennial Teacher